ENL links histone acetylation to oncogenic gene expression in AML - Wan, Liling (Nature, 2017)
Cancer cells are characterized by aberrant epigenetic landscapes and often exploit chromatin machinery to activate oncogenic gene expression programs(1). Recognition of modified histones by “reader” proteins constitutes a key mechanism underlying these processes; therefore, targeting such pathways holds clinical promise, as exemplified by the development of BET bromodomain inhibitors(2, 3). We recently identified the YEATS domain as a novel acetyllysine-binding module(4), yet its functional importance in human cancer remains unknown. Here we show that the YEATS domain-containing protein ENL, but not its paralog AF9, is required for disease maintenance in acute myeloid leukaemia (AML). CRISPR-Cas9 mediated depletion of ENL led to anti-leukemic effects, including increased terminal myeloid differentiation and suppression of leukaemia growth in vitro and in vivo. Biochemical and crystal structural studies and ChIP-seq analyses revealed that ENL binds to acetylated histone H3, and colocalizes with H3K27ac and H3K9ac on the promoters of actively transcribed genes that are essential for leukaemias. Disrupting the interaction between the YEATS domain and histone acetylation via structure-based mutagenesis reduced RNA polymerase II recruitment to ENL target genes, leading to suppression of oncogenic gene expression programs. Importantly, disruption of ENL’s functionality further sensitized leukaemia cells to BET inhibitors. Together, our study identifies ENL as a histone acetylation reader that regulates oncogenic transcriptional programs in AML and suggests that displacement of ENL from chromatin may be a promising epigenetic therapy alone or in combination with BET inhibitors for AML.